Implementasi Penjualan Kredit Terhadap Laba Perusahaan Periode 2009 – 2018 PT Sumber Alam Cipta Makmur Abadi - Teti Sumarni; Linda Daniati Melinda; Sheni Romdiah (LPPM POLITEKNIK LP3I BANDUNG, 2020)
This study aims to determine the effect of credit sales on corporate profits of PT. Sumber Alam Cipta Makmur Abadi Period 2009-2018. The data used in this study are secondary data sources in the form of credit and profit sales data from the financial statements of PT. Sumber Alam Cipta Makmur Abadi company period 2009-2018. The object of this research is PT. Sumber Alam Cipta Makmur Abadi. This type of research is quantitative research. This study uses a simple linear regression analysis method with the classic assumption test and hypothesis test. Data were collected by library research and documentation and analyzed using the SPSS version 23 application. The results of this study are credit sales affect earnings, namely credit sales variable of 0,000, which means <0.05, Based on the table above is the results of processed correlation data, It appears that the correlation coefficient correlation value or R = 0.952 or positive value indicating that sales credit has a strong relationship to profit increase of 0.952 or close to 1. While the coefficient of determination (R2) of 0.906, which means that 90.6% of credit sales are influenced by profit, while the remaining 9.4% is influenced by other variables not included in this study. The conclusion of this study is based on a simple linear regression test, meaning that the sale of credit obtained by the company can be used to measure the good or bad performance of the purchasing team and the performance of the sales team in managing all the company's resources. However, between the two teams, sales performance is the most important, because sales are the profit-making within the company